Budaya Organisasi dan Mindset Tenaga Perawat dalam Melayani Pasien GAKIN Rawat Inap di Puskesmas Campalagian - Hafid, Saktiawan; Akbar K, Fredy (Yayasan Mandar Indonesia, 2025)
Along with the shift in government paradigms and the evolving paradigm of healthcare development, health service organizations at the regional level are required to continuously improve performance and responsiveness to environmental changes. Primary Healthcare Centers (Puskesmas), as the frontline of basic healthcare services, play a strategic role in delivering equitable and quality services, particularly for low-income families (GAKIN). This study aims to describe the organizational culture and the mindset of nurses in providing inpatient services for GAKIN patients at UPT Puskesmas Perawatan Campalagian. A qualitative research approach supported by quantitative data was employed. Quantitative data were collected through questionnaires, while qualitative data were obtained from in-depth interviews and observations. The findings reveal that the dominant organizational culture is role culture (58.43%), and the most desired culture among respondents is also role culture (43.92%). The nurses’ mindset in serving GAKIN inpatients reflects a strong customer value mindset, characterized by empathy, responsibility, and patient-centered service orientation. It is recommended that organizational effectiveness and efficiency be enhanced through a gradual transformation of organizational culture from role culture to task culture by means of continuous organizational learning, while maintaining and strengthening the existing customer value mindset among nurses.